(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate clinical, paraclinical characteristics and treatment outcomes of patients with acute calculous cholecystitis undergoing laparoscopic cholecystectomy at Kien An Hospital, Hai Phong. Methods: A retrospective cross-sectional descriptive study on 52 patients diagnosed with acute cholecystitis and treated with laparoscopic cholecystectomy from January 2024 to August 2025. Results: Mean age was 46.2 ± 12.8 years, with a female-to-male ratio of 1.5:1. All patients presented with upper abdominal pain (right upper quadrant and/or epigastric). Ultrasound showed gallbladder distension and wall thickening in all cases. Surgery within 72 hours was performed in 71.1% of patients. Mean operative time was 64.1 ± 12.2 minutes (45–110 minutes). Retrograde cholecystectomy was the most common technique (75%). The conversion rate to open surgery was 7.6%. Intraoperative bleeding was the only complication (3.8%), with no postoperative complications. Mean hospital stay was 6.7 ± 1.2 days (5–10 days). Good outcomes were achieved in 87.5% of patients.